Dust bags for fly control under range conditions - R.R. Schalles; C.W. Jr. Pitts; M. McKee; J. Evans (Kansas Agricultural Experiment Station Research Reports, 1972)
Cattlemen have traditionally used various methods to control horn flies and, more recently, face flies. Many methods used require various amounts of labor and handling of cattle. Most recent efforts have stressed minimum labor. Dust bags that cattle rub to disperse insecticide is such a method. A study of the dust bag method of fly control is reported here.
Keywords: Cattlemen' s Day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station); 557; Beef; Dust bags; Fly control